2008
DOI: 10.1371/journal.ppat.1000169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Involved in Vascular Interactions of the Lyme Disease Pathogen in a Living Host

Abstract: Hematogenous dissemination is important for infection by many bacterial pathogens, but is poorly understood because of the inability to directly observe this process in living hosts at the single cell level. All disseminating pathogens must tether to the host endothelium despite significant shear forces caused by blood flow. However, the molecules that mediate tethering interactions have not been identified for any bacterial pathogen except E. coli, which tethers to host cells via a specialized pillus structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
202
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(210 citation statements)
references
References 71 publications
7
202
0
Order By: Relevance
“…These observations indicated that early-stage interaction events were essential for sustained association and vascular escape. These observations also demonstrated that microvascular interactions were dependent on B. burgdorferi proteins expressed only in the infectious strain (32). These findings are in agreement with our adhesion assay; infectious spirochetes bind more avidly to HUVEC monolayers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These observations indicated that early-stage interaction events were essential for sustained association and vascular escape. These observations also demonstrated that microvascular interactions were dependent on B. burgdorferi proteins expressed only in the infectious strain (32). These findings are in agreement with our adhesion assay; infectious spirochetes bind more avidly to HUVEC monolayers.…”
Section: Discussionsupporting
confidence: 90%
“…Protein A-immunogold labelling by using antiOspC monoclonal antibodies (G7) the spirochetes. It has been demonstrated that B. burgdorferi isolated from ticks fed on humans can express both OspA and OspC proteins and that regulation of the expression of these proteins is phenotypically different (31)(32). Human isolates of B. burgdorferi contain this protein in contrast to tick isolates which only synthesize OspA and OspB proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linkage between motility and infectivity for mammals recently was strengthened by intravital imaging of blood-borne spirochetes in mice; following attachment to the vascular endothelium, B. burgdorferi move toward and then rapidly penetrate endothelial cell junctions (63,64). Previous attempts to elucidate the mechanisms of spirochete dissemination within the arthropod have employed fixation and microscopic techniques that preclude analysis of the dynamic interactions between pathogen and vector (19,20,37).…”
Section: Discussionmentioning
confidence: 99%
“…First, B. burgdorferi has the ability to swim in highly viscous gel-like media (20,24), including the connective tissue, and this ability is abrogated in aflagellated nonmotile mutants of B. burgdorferi (29,35,48). Second, real-time intravital microscopy analysis revealed that B. burgdorferi is able to penetrate the endothelium of blood vessels and quickly disseminate from the microvasculature in living mice and that the translational motility appears to be essential for transendothelial migration (34,39). Third, a recent report indicates that B. burgdorferi transitions from a nonmotile phase to a motile phase during the period when the spirochete penetrates the tick gut basement membrane and migrates to the salivary glands of feeding ticks (14).…”
mentioning
confidence: 99%